2012
DOI: 10.1519/jsc.0b013e31822ac367
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Explosive Resistance Training Intensity Using the Rating of Perceived Exertion

Abstract: Explosive resistance training (ERT) improves older adults' strength and power, and methods to make this form of training more accessible and useful to older adults are needed. The purpose of this study was to evaluate whether the rating of perceived exertion (RPE) scale would predict a broad range of ERT intensities on the leg press with older adults. If successful, then a load-RPE relationship could be used to regulate the intensity of training loads for ERT with older adults, allowing the elimination of maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 35 publications
3
42
0
1
Order By: Relevance
“…15,16 Similarly, RPE has been used to monitor the intensity during an RT program. [17][18][19] Previous investigations have demonstrated a relationship between intensity of resistance exercise and RPE within or after sets [19][20][21][22][23][24][25][26][27] , during the session (session-RPE), and after a RT session. 28,29 While these aforementioned studies provide useful information, all employed a predetermined number of repetitions in single or multiple sets.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Similarly, RPE has been used to monitor the intensity during an RT program. [17][18][19] Previous investigations have demonstrated a relationship between intensity of resistance exercise and RPE within or after sets [19][20][21][22][23][24][25][26][27] , during the session (session-RPE), and after a RT session. 28,29 While these aforementioned studies provide useful information, all employed a predetermined number of repetitions in single or multiple sets.…”
Section: Introductionmentioning
confidence: 99%
“…The RPE has been shown to be a reliable method to quantify exercise intensity for both aerobic and resistance training (Day, McGuigan, Brice, & Foster, 2004). Row et al reported that during resistance training, a RPE score of 14-16 would elicit strength and power gains, while a score of 13 or lower would be useful for improving power in older adults (Row, Knutzen, & Skogsberg, 2012). Instructing the patient to select a load that would match a score 13 would have been a more objective way to measure exercise intensity and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of RPE anchoring have investigated the relationship between the RPE and the %1RM or %MVC [9,17,19,20,22,26,28,35,[37][38][39]. This relationship shows in Figure 2.…”
Section: Different Methods Of Anchoring the Rpementioning
confidence: 99%
“…The Borg 15-point RPE scale is a modified 6-20-point RPE scale [22,23]. This scale is presented in Table 2.…”
Section: Borg 15-point Rpe Scalementioning
confidence: 99%
See 1 more Smart Citation